Training methodology: General versus spezific visual training - Albernethy, B.; Farrow, D. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Training methods for athletes have changed regularly over the years, as coaches, sport scientists and the athletes themselves continually experiment to try and find the best types and structure of practice to hasten the acquisition of expertise and to ensure maximal performance. With the performance gains possible through the refinement of physical conditioning progressively diminishing, there has been increasing interest in how performance improvements might be gained through changes in the design of practice for skill learning. It is within this context that there has been growing interest over the past decade or so in the potential of systematic visual training as a means of hastening skill development. The purpose of this paper is to explore the evidence base for, and relative merit of, of general visual training and sport-specific visual training.